Metagenomics uncovers a core SAR11 population in brackish surface waters of the Baltic Sea - Poorna, Weerarathna Vidanage (2021)
The Baltic Sea represents one of the largest brackish ecosystems where various environmental factors control dynamic seasonal shifts in the structure, diversity, and function of the planktonic microbial communities. In this study, despite seasonal fluctuations, several bacterial populations (<2% of the total OTUs) that are highly dominant (25% of relative abundance) and highly frequently occurring (>85% of occurrence) over four seasons were identified. Mathematical models using occurrence frequency and relative abundance data were able to describe community assembly persisting over time. Further, this work uncovered one of the core bacterial populations phylogenetically affiliated to SAR11 subclade IIIa. The analysis of the hypervariable region of 16S rRNA gene and single copy housekeeping genes recovered from metagenomic datasets suggested that the population was unexpectedly evolutionarily closely related to those inhabiting a mesosaline lacustrine ecosystem rather than other marine/coastal members. Our metagenomic results further revealed that the newly-identified population was the major driver facilitating the seasonal shifts in the overall community structure over the brackish waters of the Baltic Sea. The core community uncovered in this study supports the presence of a brackish water microbiome distinguishable from other marine and freshwater counterparts and will be a useful sentinel for monitoring local/global environmental changes posed on brackish surface waters.